El Salvador : 2018 Article IV Consultation-Press Release; Staff Report and Statement by the Executive Director for El Salvador. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the real GDP of El Salvador grew above potential, at 2.3 percent in 2017, supported by lower oil prices, continued United States (U.S.) recovery, and a surge in remittances. However, El Salvador's growth continues to lag regional peers. Inflation remained low at 1 percent, anchored by dollarization. In 2018-19, growth is expected to remain above potential at 2.3 percent, reflecting the temporary acceleration of the U.S. growth from the recent U.S. tax reform and higher grant-financed investment. The fiscal deficit would further fall to 2.2 percent of GDP in 2018, as savings from the pension reform kick in, but would rise to 2.7 percent of GDP in 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet